2020
DOI: 10.24256/ideas.v8i1.1256
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Arabic in State Islamic University

Abstract: Serving as the language of al-Qur'an and everyday Islamic rituals both individually and in public congregation, Arabic is a necessary tool for all Muslims to complete their religious duties; therefore, Arabic subject is offered elsewhere starting from PAUD education to university level in our Muslim majority country. This study is going to discuss a specific aspect regarding the strategy of teaching Arabic in higher education. This specific aspect has already been our concern quite a while; it related to the ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The difficulties of using technology in teaching translation online increased during the pandemic due to additional complications of the LMS platforms. Previous research (Akmaliyah et al, 2020;Alwazna, 2021;Di Pietro et al, 2020) found that teachers were required to teach and communicate through a digital medium, while maintaining a strong sense of presence despite physical separation. About 54% of teachers had difficulty implementing online teaching (Mazlan et al, 2022).…”
Section: Difficulties Of Using Technology In Online Teaching Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties of using technology in teaching translation online increased during the pandemic due to additional complications of the LMS platforms. Previous research (Akmaliyah et al, 2020;Alwazna, 2021;Di Pietro et al, 2020) found that teachers were required to teach and communicate through a digital medium, while maintaining a strong sense of presence despite physical separation. About 54% of teachers had difficulty implementing online teaching (Mazlan et al, 2022).…”
Section: Difficulties Of Using Technology In Online Teaching Translationmentioning
confidence: 99%
“…Teachers needed to incorporate audio and video materials, online resources, and computer-aided tools into their teaching methods to ensure effective lesson delivery. Previous studies (Akmaliyah et al, 2020;Di Pietro et al, 2020;Pikhart & Al-Obaydi, 2023;Rapanta et al, 2020) highlighted challenges that encompass disparities in accessing reliable internet connections, insufficient technical support, deficiency in technology training, absence of social physical presence, as well as pedagogical issues pertaining to the adjustment of curriculum and instruction to conform to online environments. Consequently, it became necessary to enhance knowledge while acquiring online management skills, and incorporate virtual thinking methodologies, and innovative pedagogies while exploring virtual reality technology (Aroles & Küpers, 2021;Basilaia et al, 2020;Xiao & Muñoz, 2020).…”
Section: Introductionmentioning
confidence: 99%